Body Image, Socio-Cultural Factors and Psychological Health among Adolescents in Accra, Ghana Ghana - Asah-Ayeh, V. (University of Ghana, 2017)
This thesis examines how socio-cultural factors influence body dissatisfaction, body image, self-esteem and psychological distress among adolescents in Accra, Ghana. Mixed-method approach was used to gather data through cross-sectional survey and focused group discussions. Sample for the survey and the focused group discussions consisted of 358 and 62 adolescents respectively. They were conveniently sampled from selected districts in the Greater Accra region. The quantitative data was analysed using ANOVA, Pearson r and MANOVA and the qualitative data was analysed using thematic analysis. Findings from the quantitative component showed that body dissatisfaction increases psychological distress and decreases body esteem among the adolescents. Adolescents who were satisfied with their body adopted three coping strategies (i.e. avoidance, positive-rational and appearance fixing); whereas those who were dissatisfied with their bodies adopted two (i.e., avoidance and appearance fixing). The qualitative findings showed that family posed as a severe stressor to adolescents’ body image perceptions and pressured them to engage in body fixing. Adolescents also engaged in Selfie-taking mainly for social comparison and self-evaluations. In conclusion, socio-cultural factors influenced body image perceptions and psychological health among the adolescents at different levels of analysis, ranging from intra-personal level, interpersonal level, family and societal levels. The implications of the results of the study are discussed in relation to creating safe social spaces for improving mental health of adolescents within the context of how they experience their bodies.
Thesis (MPhil)
Keywords: Body Image; Socio-Cultural; Factors and Psychological; Adolescents; Accra; Ghana